2017
DOI: 10.1590/2359-3997000000255
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subclinical atherosclerosis evaluated by carotid intima-media thickness in asymptomatic young women with type 1 diabetes mellitus

Abstract: Objective: This study aimed to evaluate the occurrence and clinical predictors of subclinical atherosclerosis in asymptomatic, young adult women with type 1 DM. Subjects and methods: The study included 45 women with type 1 diabetes mellitus (DM) (aged 36 ± 9 years) who underwent carotid Doppler ultrasound evaluation to determine the carotid artery intima-media thickness (CIMT) and to assess the occurrence of carotid artery plaques. Insulin sensitivity was assessed by estimated glucose disposal rate (eGDR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Carotid intima-media thickness (CIMT) is a well-established predictor for the risk of subclinical atherosclerosis [14]. Here, we found a positive correlation between serum miR-186-5p level and CIMT in atherosclerosis patients (r = 0.6634, p < 0.001; Fig.…”
Section: Correlation Of Mir-186-5p With Cimt In Atherosclerosis Patientssupporting
confidence: 52%
“…Carotid intima-media thickness (CIMT) is a well-established predictor for the risk of subclinical atherosclerosis [14]. Here, we found a positive correlation between serum miR-186-5p level and CIMT in atherosclerosis patients (r = 0.6634, p < 0.001; Fig.…”
Section: Correlation Of Mir-186-5p With Cimt In Atherosclerosis Patientssupporting
confidence: 52%
“…A research looking at CVD risk trajectories from childhood to adulthood found that many of those who had consistently high BMIs during the life-course were better protected from carotid intima-media thickening if they were physically active 35 . Furthermore, in additional studies, no association was found between BMI and carotid atherosclerosis in non-diabetic 36 as well as diabetic patients 5,37 . We are not aware of any published evidence on the association of carotid elastography and…”
Section: Discussionmentioning
confidence: 86%
“…[15][16][17]37,38 In the same line, one study has identified eGDR as a predictor of subclinical atherosclerosis, but it only included 45 women (mean age 36.2 ± 9.5 years). 19 In opposition, a recent study performed with 298 young individuals with T1D (mean (Figure 2), eGDR was the only IR marker which was associated with both the maximum height and presence of ≥2 plaques. Altogether, these findings suggest that IR assessed by eGDR could be a better marker of advanced atherosclerosis (plaque-related variables) rather than of its earlier stages (IMT-related variables) in this population.…”
Section: 405mentioning
confidence: 76%
“…Former studies evaluating IR as a predictor of increased carotid intima-media thickness (IMT) and/or carotid plaque presence are scarce. 18,19 Considering this background, our study aimed to test the association between IR, evaluated by both non-specific [metabolic syndrome (MetS) criteria according to the harmonized definition proposed by the main scientific societies in 2009 20 ] and specific (eGDR formula as a well-validated T1D-IR indicator 14 ) measures, and preclinical carotid atherosclerosis in a broad range of adults with T1D at high CVD risk.…”
Section: Introductionmentioning
confidence: 99%